MINIMNYA PERHATIAN ORANG TUA DAN IMPLIKASINYA TERHADAP DISIPLIN SISWA SEKOLAH DASAR - Ayumi Vesaka; Santi Eka Putri; Syofiani; Rieke Alyusfitri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the impact of limited parental attention on student discipline in elementary schools and to understand its implications on student behavior and learning motivation. This research employed a descriptive qualitative case study approach conducted at SDN 26 Lubuk Alung. Data were collected through interviews, observations, and documentation and analyzed using source and technique triangulation to ensure validity. The results indicate that students who receive minimal routine attention from parents tend to exhibit lower discipline, including tardiness, incomplete assignments, and reduced cooperation in class. Limited parental attention also negatively affects students’ learning motivation and their ability to internalize school rules. The study highlights the importance of active collaboration between schools and parents through regular communication, supervision, and positive reinforcement to sustainably develop student discipline and motivation. The findings imply that parental involvement is integral to school efforts in shaping students’ character and discipline